How to effectively use interactivity with interactive data visualization on groups with different literacy levels - Oliveira, Mônica Carvalho Generini de (2021)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence